Impedance Spectroscopy of n-CdTe/p-CdMnTe/p-GaAs Diluted Magnetic Diode - Yahia, I. S.; AlFaify, S.; Yakuphanoğlu, Fahrettin; Chusnutdinow, S.; Wojtowicz, T.; Karczewski, G. (Springer, 2015)
n-CdTe/p-CdMnTe/p-GaAs diluted magnetic diode was grown by molecular beam epitaxy technology. The forward- and reverse-bias capacitance-voltage (C-V), conductance-voltage (G-V), series resistance-voltage (R (s)-V), impedance-voltage (Z-V), and phase-voltage (theta-V) characteristics of this diode have been analyzed in the frequency range of 5 kHz to 1 MHz at room temperature. Both the density of interface states (N (ss)) and series resistance (R (s)) are strongly frequency dependent and decrease with increasing frequency. The values of the built-in potential (), the doping concentration (), and the barrier height () of the diode were calculated at different frequencies. Our experimental results revealed that both the series resistance and interface state density must be taken into account in studying the impedance spectroscopy on heterojunction diodes to understand their performance for electronic and optoelectronic applications. Diluted magnetic semiconductors are promising materials for future technology.
Keywords: Diluted magnetic diode; multilayers; n-CdTe/p-CdMnTe/p-GaAs; impedance spectroscopy; electrical properties; interface state density